2011
DOI: 10.1039/c1cc10665a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal facet engineering of semiconductor photocatalysts: motivations, advances and unique properties

Abstract: Crystal facet engineering of semiconductors has become an important strategy for fine-tuning the physicochemical properties and thus optimizing the reactivity and selectivity of photocatalysts. In this review, we present the basic strategies for crystal facet engineering of photocatalysts and describe the recent advances in synthesizing faceted photocatalysts, in particular TiO(2) crystals. The unique properties of faceted photocatalysts are discussed in relation to anisotropic corrosion, interaction dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
701
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 919 publications
(715 citation statements)
references
References 216 publications
(214 reference statements)
13
701
1
Order By: Relevance
“…It has been demonstrated that exposed high-energy surfaces are crucial for improving the chemical activity of TiO 2 (refs 34,35). Although the surface energy of anatase {010} (0.53 J m À 2 ) was calculated to be between those of {001} (0.90 J m À 2 ) and {101} (0.44 J m À 2 ), no {010} appears in the equilibrium shape of anatase crystals or nanostructures 35 . The presence of the high percentage of exposed high-energy anatase {010} surfaces in the ultrathin 2D TiO 2 nanosheets would endow them with high chemical activity 35 .…”
Section: Synthesis and Microscopy Characterizations Of 2d Nanosheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that exposed high-energy surfaces are crucial for improving the chemical activity of TiO 2 (refs 34,35). Although the surface energy of anatase {010} (0.53 J m À 2 ) was calculated to be between those of {001} (0.90 J m À 2 ) and {101} (0.44 J m À 2 ), no {010} appears in the equilibrium shape of anatase crystals or nanostructures 35 . The presence of the high percentage of exposed high-energy anatase {010} surfaces in the ultrathin 2D TiO 2 nanosheets would endow them with high chemical activity 35 .…”
Section: Synthesis and Microscopy Characterizations Of 2d Nanosheetsmentioning
confidence: 99%
“…Although the surface energy of anatase {010} (0.53 J m À 2 ) was calculated to be between those of {001} (0.90 J m À 2 ) and {101} (0.44 J m À 2 ), no {010} appears in the equilibrium shape of anatase crystals or nanostructures 35 . The presence of the high percentage of exposed high-energy anatase {010} surfaces in the ultrathin 2D TiO 2 nanosheets would endow them with high chemical activity 35 . For the exposed surfaces of ZnO, Co 3 O 4 and WO 3 , however, no such high-energy exposed surfaces were observed.…”
Section: Synthesis and Microscopy Characterizations Of 2d Nanosheetsmentioning
confidence: 99%
“…Thus, certain facets of a semiconductor prefer reduction while others favour oxidation [18][19][20] . However, reports on the reduction and oxidation reaction facets on the same semiconductor crystal (such as TiO 2 ) were often contradictory in the literature [21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…In addition, the difference in surface energies of the conduction and valence bands of different crystal facets of titania can promote the separation of electrons and holes [12]. The shape of an anatase titania single crystal, which determines the type of the exposed crystal facet, has recently been recognized as a potential key factor influencing photocatalytic efficiency and selectivity [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%